School Health Education Services and Reproductive Health-Seeking Behaviour of Junior High School Adolescent Females in Bawku West District, Upper East Region - Aawulenaa, D. (University of Ghana, 2016)
This study explored the school health education programme and the reproductive health-seeking behaviour of adolescents in selected Junior High Schools in the Bawku West District. It touched on the scope of the school health education programme, knowledge of female students on sexual and reproductive health issues, their health-seeking behaviour and the factors that hinder adolescents from seeking formal health care. The study adopted a qualitative method, using criterion, convenient and purposive sampling approaches to recruit fifty-nine Junior High School females and four community health officers for six focus group discussions (FGDs) and four in-depth interviews (IDIs) respectively. Semi-structured interview guides, a note book and an audio tape recorder were used for the data collection. Thematic analysis of the data was done by coding and categorizing the data into themes for easy interpretation. The findings of the study were that, the School Health Education Programme provides varied health information ranging from personal hygiene to environmental hygiene, through to sexual and reproductive health issues. The result showed that, junior high school females were generally knowledgeable on sexual and reproductive health issues such as menstrual hygiene management, teenage pregnancy, family planning, unsafe abortion practices, signs and symptoms of sexually transmitted infections (STIs) and ways to prevent them. The study also identified stigma, misconception and high cost of services as some of the factors that hinder adolescents from seeking sexual and reproductive health services. The study recommends a strong support and strengthening of policy implementation in professional training on confidentiality, customer care and effective counseling to correct some misconceptions or myths that adolescents have about family planning methods. Gleaning from the study, there is the need for rigorous advocacy on responsible parenting to curb some of the reproductive challenges that adolescents face. The study also recommends future research on the subject matter with out of school adolescents, and with the broader adolescent group of 10-19 years in the same district or a different setting using a mix method.
Theses (MPh.) - University Of Ghana, 2016
Keywords: Adolescent; school health; health-seeking behaviour; sexual and reproductive health